Mediação em geografia: práticas de professores no ensino fundamental na cidade de Cruzeta-RN - Oliveira, João Paulo de (2014)
This dissertation is inside a study on the intercession of teachers in Geography lessons, from classes in the 6th grade of Elementary School. This study was conducted in an Elementary Municipal school named Cônego Ambrósio Silva , located in Cruzeta, a city from the state of Rio Grande do Norte, in Brazil. In the text, we discuss about the teaching and learning in Geography in the reality that was researched on this process, highlighting the pedagogical aspects and tools appropriate by teachers. Among the aspects discussed are: the teacher-student relationship in the context of the school and, in this case, specifically the classroom environment; the context in which the teachers work, which is a challenge because it directly influences the teaching activities in their daily teaching. Thus, we realize that the development of teaching activity, and there are some challenges that teachers seek to overcome from the strategies they use. Extracurricular problems or problems arising from socioeconomic and cultural aspects are challenges that make it more complex to mediate what it is planned to achieve the teaching and learning process. From the fieldwork that was done, we seek to answer the questions initially raised about teachers atittudes in Geography. Among them it could be pointed out: What are the educational supports that appropriates the teacher to teach Geography? What are the features of the geography teacher's profile in the city of Cruzeta-RN? How is going to approach the content of the school landscape chosen for this research? And how the approach of the content of the school landscape chosen for this research is taking place? How is it happening the approach by the teachers of Geography about the topics of landscapes in the school that was intestigated? From the research on these issues, we emphasize that the study presents characteristics of a qualitative nature, because we used the method of participatory research in which, methodologically, we conducted observations over a period of three months and also some semi-structured interviews were used. We believe it is important to hear what teachers have to say about their choices and ways of teaching strategies, methodologies of teaching Geography. Thus, we prefer to highlight a few moments of talking with the teachers in this study. We consider, therefore, that the contemporary teacher of geography needs to think about his/her practice, so that is consciously planned, accordingly, constituting it as an intentional action. The survey also revealed that the local context of the school is, for the most part, a strong component that roots the teachers practices. Thus, mediation conducted by teachers of Geography, indicated by the researchers of education, may be to discuss the contents, raising the desire of students to discover the relationship we have such knowledge with their reality.